Hubungan motivasi kontrol pasien dengan kepatuhan kontrol orthodonti cekat pada masa pandemi COVID-19 - Anisa Aini Fitri; Suharyono Suharyono; Furaida Khasanah (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2020)
Background: The motivation to control patients for fixed orthodontic treatment usually comes from themselves or from outside that affects the expected goals. During the Covid-19 pandemic, dental services, especially orthodontic treatment, were disrupted. This treatments requires a long and continuous time and process,in order to obtain maximum results, patient compliance is required to control. Research objectives: To know the correlation between patients motivation control and compliance of fixed orthodontic appliance control in pandemic of Covid-19 times at clinics in Yogyakarta. Research method: This research method is analytic survey with cross sectional approach. The population of study was fixed orthodontics users who visited the dental clinic at January-November 2020 and used fixed orthodontics for 12 months. Sampling using accidental sampling technique data collection using primary data taken from the results of questionnaires and secondary data taken and report of patient visits data analysis using The Kendalls Tau test. Research results: The gender of female had strong control motivation as much as16 people (53.3%), higher than 7 people (23.3%), while the adherence of female controls had adherence criteria as many as 18 people (60.0%) were higher thanthat of men. Male as many many as 8 people (26.7%). The result showed a significant relationship between patient control motivation and adherence to fixedorthodontic control during the Covid-19 pandemic at aclinic in Yogyakarta, with a value of p=0.033<0.05, while the correlation coefficient value was 0.293. Conclusion: Patient control motivation has a fairly close relationship with adherence to fixed orthodontic controls during the Covid-19 pandemic, becausethe higher the level of patient control motivation, the higher the patients compliance to perform fixed orthodontic control.